2013
DOI: 10.1103/physrevlett.111.036103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Contact Resonance of Microspheres with Surface Acoustic Waves

Abstract: We study the interaction of surface acoustic waves (SAWs) with a contact-based vibrational resonance of 1 μm silica microspheres forming a two-dimensional granular crystal adhered to a substrate. The laser-induced transient grating technique is used to excite SAWs and measure their dispersion. The measured dispersion curves exhibit "avoided crossing" behavior due to the hybridization of the SAWs with the microsphere resonance. We compare the measured dispersion curves with those predicted by our analytical mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
160
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(174 citation statements)
references
References 34 publications
13
160
1
Order By: Relevance
“…The mode labeled V corresponding to the most prominent peak in the spectra, as shown in Fig. 2(e), was previously identified as the vertical contact resonance mode [7,9,10]. Figure 2(e) also shows small peaks to either side of the V-mode peak which we assigned to horizontal-rotational modes labeled HR and RH following Ref.…”
Section: B Experimentsmentioning
confidence: 97%
See 2 more Smart Citations
“…The mode labeled V corresponding to the most prominent peak in the spectra, as shown in Fig. 2(e), was previously identified as the vertical contact resonance mode [7,9,10]. Figure 2(e) also shows small peaks to either side of the V-mode peak which we assigned to horizontal-rotational modes labeled HR and RH following Ref.…”
Section: B Experimentsmentioning
confidence: 97%
“…The initial efforts focused on the vertical contact resonance of microspheres, arising due to contact with the substrate, and its interaction with surface acoustic waves (SAWs). In these initial studies, the observed phenomena, such as an avoided crossing in the Rayleigh SAW dispersion [7] and the resonant attenuation of SAWs by microspheres [9], could be well accounted for by a simple model where microspheres did not interact with each other [7]. Refined measurements of the resonant attenuation of SAWs * avegaflick@gmail.com † maznev@mit.edu revealed horizontal-rotational modes enabled by interparticle interactions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case is exemplified by surface Rayleigh waves on a solid half-space. The interaction of vertical surface oscillators with a Rayleigh wave has been studied theoretically [17,18] and recently observed experimentally [5]. In this case a classic avoided crossing takes place.…”
Section: Discussionmentioning
confidence: 99%
“…In acoustics, this phenomenon has attracted renewed attention more recently [2][3][4][5][6] in the context of sound propagation in artificial media referred to as locally resonant metamaterials [2]. It is well known that in a medium containing resonant inclusions [2,[7][8][9][10][11][12], propagating waves hybridize with the local resonance resulting in an avoided crossing bandgap, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%